2004
DOI: 10.1128/jvi.78.9.4561-4565.2004
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic Effects of Immunoglobulin GM and KM Allotypes on Outcome of Infection with Hepatitis C Virus

Abstract: Immunoglobulin GM and KM allotypes-genetic markers of ␥ and chains, respectively-are associated with immune responsiveness to several infectious pathogens and with survival in certain viral epidemics. We hypothesized that GM and KM allotypes affect the outcome of hepatitis C virus (HCV) infection. To test this hypothesis, we serologically allotyped 100 persons with well-documented clearance of HCV infection and 198 matched persistently infected persons. None of the GM or KM phenotypes by itself was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 40 publications
1
31
1
Order By: Relevance
“…This would suggest a higher prevalence of GM23 in subjects with persistent HCV infection compared to those who have cleared the virus. This appears to be the case in a study population we reported on earlier (8). Among subjects with persistent HCV infection (n ϭ 196), there were 51 subjects (26%) CORE PROTEIN AND IgG 2 ALLOTYPES carrying the GM23 allele, while among patients that cleared the virus (n ϭ 99), there were 22 subjects (22%) carrying the GM23 allele.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…This would suggest a higher prevalence of GM23 in subjects with persistent HCV infection compared to those who have cleared the virus. This appears to be the case in a study population we reported on earlier (8). Among subjects with persistent HCV infection (n ϭ 196), there were 51 subjects (26%) CORE PROTEIN AND IgG 2 ALLOTYPES carrying the GM23 allele, while among patients that cleared the virus (n ϭ 99), there were 22 subjects (22%) carrying the GM23 allele.…”
Section: Discussionmentioning
confidence: 44%
“…Among the factors influencing the outcome of HCV infection, the host genetic factors are thought to play a predominant role (4,6). We have previously reported involvement of immunoglobulin (Ig) GM and KM allotypes-genetic markers of ␥ and chains, respectively-in the outcome of HCV infection (8). The mechanisms underlying this association are not completely understood.…”
Section: Most Common Causes Of Liver Disease In Thementioning
confidence: 98%
“…Individuals with the IGHG * bfn haplotype are high producers of antibodies against encapsulated bacteria and in vaccination with bacterial polysaccharides [22,23]. The influence of viral particles acting as FcγRs with preference of binding to different IGHG (Fcγ) allotypes [25,26,27] is important and can be applied also to allergic disease, possibly related to exacerbations. Severe infections in infants with respiratory syncytial virus are associated with the IGHG * bf-n/ * bf-n diplotype and the IGHG2 * -n alleles [35].…”
Section: Discussionmentioning
confidence: 99%
“…Allergens, bacteria [22,23] and virus [25,26,27] affect IGHG genes of individuals differently and relate to the diseases as allergy [7,8,9,10,11,12], primary immunodeficiency [28], autoimmunity [29,30] and malignancy [31,32]. …”
Section: Introductionmentioning
confidence: 99%
“…They also influence immune responsiveness to infectious epitopes as well as to certain autoantigens (10,25,26,28,29). Of particular relevance here, certain GM and KM determinants interact to influence the outcome of HCV infection (22). These observations led us to hypothesize that GM and KM allotypes may contribute to the generation of anti-LKM1 autoantibodies in HCV-infected subjects.…”
mentioning
confidence: 99%